(untitled) (International Journal of Engineering and Computer Science, 2018)
The rapid development of multimedia and internet allows for wide distribution of digital media data. It becomes much easier to edit, modify and duplicate digital information. Besides that, digital documents are also easy to copy and distribute, therefore it will be faced by many threats. It is a big security and privacy issue, it become necessary to find appropriate rotation because of the significance, accuracy and sensitivity of the information. Steganography and Cryptography are considered as one of the techniques which are used to protect the important information, but both techniques have their pro’s and con’s. In this paper we have proposed a novel approach to hide the data in audio signals based on LSB technique. Performance of the proposed system is evaluated on various parameters and is compared with the existing systems.